2011
DOI: 10.1099/ijs.0.025221-0
|View full text |Cite
|
Sign up to set email alerts
|

Flavitalea populi gen. nov., sp. nov., isolated from soil of a Euphrates poplar (Populus euphratica) forest

Abstract: A novel strain, designated HY-50RT , isolated from soil of a Euphrates poplar (Populus euphratica) forest in Xinjiang, China, was characterized using a polyphasic taxonomic approach. Cells of the isolate were Gram-reaction-negative, strictly aerobic, rod-shaped, non-motile, oxidase-negative and catalase-positive. Phylogenetic analysis based on 16S rRNA gene sequences showed that the isolate was a member of the phylum Bacteroidetes, its closest relatives being Niastella populi THYL-44 T (93.6 % similarity), Fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 32 publications
(25 reference statements)
4
28
0
Order By: Relevance
“…S1). The isoprenoid quinone of strain KIS20-3 T was predominantly MK-7, which was consistent with that of the type strains of F. populi and F. gansuensis (Wang et al, 2011;Zhang et al, 2013). The DNA G+C content of strain KIS20-3 T was 55.7 mol%, which was higher than those (46.8-47.1 mol%) of the type strains of F. populi and F. gansuensis.…”
Section: Ferruginibacter Alkalilentus Hu1-gd23 T (Fj177530)mentioning
confidence: 58%
See 1 more Smart Citation
“…S1). The isoprenoid quinone of strain KIS20-3 T was predominantly MK-7, which was consistent with that of the type strains of F. populi and F. gansuensis (Wang et al, 2011;Zhang et al, 2013). The DNA G+C content of strain KIS20-3 T was 55.7 mol%, which was higher than those (46.8-47.1 mol%) of the type strains of F. populi and F. gansuensis.…”
Section: Ferruginibacter Alkalilentus Hu1-gd23 T (Fj177530)mentioning
confidence: 58%
“…The type species of the genus Flavitalea, Flavitalea populi, was isolated from a forest soil, and characterized as Gram-reaction-negative, strictly aerobic, rod-shaped, non-motile, oxidase-positive and catalasepositive. It contained menaquinone 7 (MK-7) as the predominant respiratory quinone, and iso-C 15 : 1 G, iso-C 15 : 0 and iso-C 17 : 0 3-OH as major fatty acids, but lacked flexirubin-like pigments (Wang et al, 2011). Later, Flavitalea gansuensis, which was isolated from arid soil, was validly published as a new member within the genus Flavitalea, and shared most of the generic properties of F. populi (Zhang et al, 2013).…”
mentioning
confidence: 99%
“…At the time of writing, the family Chitinophagaceae includes 14 genera: Chitinophaga (Kämpfer et al, 2006), Ferruginibacter (Lim et al, 2009), Filimonas (Shiratori et al, 2009), Flavihumibacter (Zhang et al, 2010), Flavisolibacter (Yoon & Im, 2007), Flavitalea (Wang et al, 2011), Hydrotalea (Kämpfer et al, 2011, Lacibacter (Qu et al, 2009), Niabella (Kim et al, 2007), Niastella (Weon et al, 2006), Parasegetibacter (Zhang et al, 2009), Sediminibacterium (Qu & Yuan, 2008), Segetibacter and Terrimonas (Xie & Yokota, 2006).…”
mentioning
confidence: 99%
“…Fatty acids were saponified, methylated and extracted using the standard protocol of the MIDI Sherlock Microbial Identification System (version 6.0), analysed by GC (Yoon & Im, 2007); 9, Parasegetibacter luojiensis CCTCC AB 208240 T (Zhang et al, 2009); 10, Niabella aurantiaca DSM 17617 T (Kim et al, 2007); 11, Segetibacter koreensis KCTC 12655 T Kämpfer et al, 2011;Wang et al, 2011); 12, Niastella koreensis DSM 17620 T (Weon et al, 2006); 13, Sediminibacterium salmoneum CGMCC 1.6845 T (Qu & Yuan, 2008;Wang et al, 2011;Kim et al, 2013) (Hewlett Packard 6890N) and identified using the TSBA6 database of the Microbial Identification System (Sasser, 1990).…”
mentioning
confidence: 99%
“…Single carbon source assimilation by strain DHOA34 T Table 1. Differential phenotypic characteristics between strain DHOA34 T and the type strains of related genera of the family Chitinophagaceae Strains: 1, DHOA34 T ; 2, Flavisolibacter ginsengiterrae Gsoil 492 T ; 3, Cnuella takakiae RG1-1 T ; 4, Chitinophaga terrae KP01 T (1-4, data from this study); 5, Flavitalea populi HY-50R T (Wang et al, 2011); 6, Sediminibacterium goheungense HME7863 T (Kang et al, 2014). All strains are negative for chitinase, glucose fermentation, indole and H 2 S production, reduction of nitrates to nitrites/nitrogen, arginine dihydrolase, and assimilation of capric acid, malic acid, L-arabinose, gluconate and citric acid.…”
mentioning
confidence: 99%